Analysis of Soybean Raw Material Inventory Control Using The EOQ Method in Tempe MSMS in Malang City Case Study at Tempe Chips Industry Center Association - Veronika Arma; Cakti Indra Gunawan; Yuni Setyawati (IRDH International Journal of Social Sciences & Humanities, 2026)
There are still many fundamental problems being faced, particularly in terms of production and the availability of raw materials. One of the most significant obstacles is the supply of soybeans as the main ingredient for tempeh production, which is largely still dependent on imports. Dependence on imports causes soybean prices to be highly unstable, directly affecting the production costs of tempeh SMEs. Research Objective: To examine the application of the EOQ method in controlling the inventory of soybean raw materials in tempeh SMEs in Malang City. This is a quantitative study, and the data collection technique uses both primary and secondary data methods. Research Results: The management of raw material inventory in Kampung Sanan, located in Purwantoro Village, Blimbing Subdistrict, Malang City, has not been running well. There are still many mistakes in managing raw materials, namely soybeans and yeast. This can be seen from the number of unmet demands in 2023, which amounted to 122,715 units, and in 2024, which amounted to 1,257 units. There are still demands that were not fulfilled due to a shortage of raw materials during production. There was still a shortage of raw materials in 2023, with 40,495 kg of soybeans and 80,991 kg of yeast, and in 2024, 79,434 kg of soybeans and 80,991 kg of yeast. In daily operations, raw materials often run out or experience stockouts. This is due to inaccurate calculations of the required amount of raw materials and the timing of orders, resulting in the inability to meet all customer demands.